2018
DOI: 10.1016/j.jaci.2018.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Solute carrier family 9, subfamily A, member 3 (SLC9A3)/sodium-hydrogen exchanger member 3 (NHE3) dysregulation and dilated intercellular spaces in patients with eosinophilic esophagitis

Abstract: SLC9A3 plays a functional role in DIS formation, and pharmacologic interventions targeting SLC9A3 function may suppress the histopathologic manifestations in patients with EoE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…Genome-wide association studies have identified epithelial barrier-related genes such as FLG and CAPN14 (2,3). Transcriptomic studies have identified others associated with disease, including SPINK7 and SLC9A3 (4,5). Histologic and ultrastructural studies revealed increased intercellular spaces and reduced desmosomal infrastructure (6)(7)(8), functional studies identified increased impedance (9), and molecular examinations determined key roles for inflammatory molecules including the cytokine IL-13 in diminishing epithelial barrier (2,4,10).…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies have identified epithelial barrier-related genes such as FLG and CAPN14 (2,3). Transcriptomic studies have identified others associated with disease, including SPINK7 and SLC9A3 (4,5). Histologic and ultrastructural studies revealed increased intercellular spaces and reduced desmosomal infrastructure (6)(7)(8), functional studies identified increased impedance (9), and molecular examinations determined key roles for inflammatory molecules including the cytokine IL-13 in diminishing epithelial barrier (2,4,10).…”
Section: Introductionmentioning
confidence: 99%
“…IL-13 is highly up-regulated in inflamed tissue and regulates the expression of several key molecules ( Blanchard et al, 2010 ). Studies have reported altered expression of two ion transporters [NHE3 and anoctamin 1 (ANO1)] in EoE ( Zeng et al, 2018 ; Vanoni et al, 2020 ). The mRNA and protein expression of both NHE3 and ANO1 significantly increases in biopsy samples obtained from EoE patients and in IL-13-treated OECs and model systems.…”
Section: Role Of Ion Transporters Under Pathological Conditionsmentioning
confidence: 99%
“…The mRNA and protein expression of both NHE3 and ANO1 significantly increases in biopsy samples obtained from EoE patients and in IL-13-treated OECs and model systems. Both NHE3 and ANO1 are up-regulated by the transcription factor signal transducer and activator of transcription 6 (STAT6) and are positively correlated with disease progression ( Zeng et al, 2018 ; Vanoni et al, 2020 ). Pharmacological NHE3 inhibition blocks IL-13-induced DIS formation, indicating the involvement of NHE3 in DIS formation ( Zeng et al, 2018 ).…”
Section: Role Of Ion Transporters Under Pathological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Wright et al 10 preliminarily reported similarities between esophageal overexpression of GATA-3 and T-bet in patients with EoE and proton pump inhibitor-responsive esophageal eosinophilia. 9,10 Zeng et al 11 aimed to understand the response of the esophagi of patients with EoE to acid; the team focused on the acid-protective mechanisms centered around carrier family 9, subfamily A, member 3 (SLC9A3), and its ability to regulate intracellular pH, as well as formation of dilated intercellular spaces (DISs), because this is a process germane to the esophageal barrier impairment seen in patients with EoE. SLC9A3 was the most dysregulated esophageal gene central to regulating intracellular pH, and its increased expression positively correlated with disease severity, as defined by the number of eosinophils/high-power field and the presence of DISs.…”
Section: Eoementioning
confidence: 99%